International Law: An Interview with Oscar Schachter - Schachter, Oscar (Tufts Archival Research Center, 2005)
Volume 9, Issue 1. Winter Oscar Schachter is the Hamilton Fish Professor of International Law and Diplomacy at the Columbia University School of Law, andsince1978 has been Editor-in-Chief of the American Journal of International Law. Prior to 1975, he served as Director of the legal division of the United Nations and as Director of Studies at the U.N. Institute for Training and Research. In the following interview, professor Schachter draws on his experience as both a scholar and a practitioner to provide a general overview of some of the key issues in international law, including the theoretical basis of the international legal order, the process by which that order evolves, contending approaches to treaty interpretation, and the role of international organization in the changing world order.